(untitled) (Journal of Economic Research & Business Administration, 2016)
Increase of efficiency and competitiveness of national economy is connected with employment of ablebodied population. The special role is played by employment of youth, which is one of social economic active, a segment of the population, possessing innovative and creative potential. Employment problems, support and development of professional competitiveness of youth in labor market is a strategic priority of a state policy. There is the positive tendency in employment of the population in Kazakhstan. However, the analysis shows that in 20102014 the population of the country with the higher and secondary professional education has the trend to increase. Tendencies and the structural changes of employment of youth having the higher and secondary professional education, the reasons of instability and imbalance of labor market, reveal concrete recommendations about optimization of structure of training of arts, technical and secondary professional education are offered in this article. We considered the best practices of the foreign countries on employment recognized as the world community as an effective remedy of fight against unemployment recommendations about formation and development of youth business, publicprivate partnership in preparation and employment of young shots are made